Blood profile of white rats (Rattus norvegicus): Safety study of stigmasterol compounds from beluntas leaves (Pluchea indica) as antifertility - Susetyarini, Eko; Latifa, Roimil; Nurtjahyani, Supiana Dian; Nurrohman, Endrik (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
This study aimed to examine the blood smear profile of male white rats after treatment with various doses of stigmasterol from Pluchea indica leaves. The experimental study used the post-test control design group. The study was conducted in the several accredited laboratories in Malang and Bandung cities. The study was conducted from June to September 2024. The research sample of stigmasterol from P. indica leaves came from the UPT materia medica of Batu City. The sampling technique was purposive random sampling. Three doses of stigmasterol (0.125 mg/kg bw, 0.25 mg/kg bw, 0.5 mg/kg bw), and control (aquades) with seven replications. Observations of preparations for each treatment group used a binocular microscope. Photos of the observation results were analyzed for cell shape, and the number of visible white blood cells was calculated. Data analysis used one-way ANOVA and Duncan’s further test. The results showed a stigmasterol dose hadtigmasteroland number of erythrocytes in the blood of white rats. The findings of this study were that dose 3 (0.5 mg/kg bw) had the lowest number of leukocytes, and further research is needed as a safe dose of the stigmasterol compound in P. indica leaves, which has the potential as a natural antifertility drug.